2010
DOI: 10.1099/mic.0.036442-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of conjugated linoleic acids and 18 : 1 fatty acids by ruminal bacteria: products and mechanisms

Abstract: Cultures of ruminal bacteria known to metabolize unsaturated fatty acids were grown in medium containing 50 mg ml "1 of geometric and positional isomers of conjugated linoleic acid (CLA) or 18 : 1 fatty acids and 37.4 % deuterium oxide to investigate the mechanisms responsible for fatty acid metabolism. Butyrivibrio fibrisolvens JW11 converted cis-9,trans-11-18 : 2 and trans-9,trans-11-18 : 2 to trans-11-18 : 1 as the main product, labelled at C-9, and metabolized trans-10,cis-12-18 : 2 to trans-10-18 : 1, lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
118
3
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(144 citation statements)
references
References 48 publications
15
118
3
8
Order By: Relevance
“…Although the OLI diet provides a greater amount of c 9-18:1 than the PALM diet (Table 2), the content of this FA in the OLI meat fat did not differ from that of the PALM meat fat. These results could be explained by the abundance of 18:0 in the PALM diet, which reaches the adipose tissue and, as mentioned previously, is partly converted into c 9-18:1 via Δ9 desaturase, while the c 9-18:1 provided by the OLI diet is susceptible to isomerization in the rumen and the formation of several trans-monoenes isomers (Mosley et al, 2002;McKain et al, 2010).…”
Section: Meat Qualitymentioning
confidence: 72%
See 2 more Smart Citations
“…Although the OLI diet provides a greater amount of c 9-18:1 than the PALM diet (Table 2), the content of this FA in the OLI meat fat did not differ from that of the PALM meat fat. These results could be explained by the abundance of 18:0 in the PALM diet, which reaches the adipose tissue and, as mentioned previously, is partly converted into c 9-18:1 via Δ9 desaturase, while the c 9-18:1 provided by the OLI diet is susceptible to isomerization in the rumen and the formation of several trans-monoenes isomers (Mosley et al, 2002;McKain et al, 2010).…”
Section: Meat Qualitymentioning
confidence: 72%
“…In the rumen, c 9,t 11-18:2 is produced during biohydrogenation of c 9,c12-18:2n-6 (Griinari and Bauman, 1999). In vitro studies have shown that during the biohydrogenation of oleic acid, small amounts of t 11-18:1 are also produced (Mosley et al, 2002;McKain et al, 2010). The c 9,t 11-18:2 present in adipose tissue comes from ruminal biohydrogenation of c 9,c12-18:2n-6 (Griinari and Bauman, 1999) Vegetable oils and meat quality in beef and from the endogenous synthesis from t 11-18:1.…”
Section: Meat Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Incubations with mixed or pure cultures of rumen bacteria demonstrated that OA can be biohydrogenated to 18:0 (Harfoot and Hazlewood, 1988), whereas more recent studies indicated that metabolism of OA in vitro results in the formation of oxygenated fatty acids (10-OH 18:0 and 10-O 18:0) and numerous trans-18:1 intermediates with double bonds at positions D6-D16 (Mosley et al, 2002;Jenkins et al, 2006;McKain et al, 2010; Figure 1). Direct comparisons indicate that the extent of biohydrogenation of OA is also lower compared with LA and LNA and typically varies between 58% and 87% (Loor et al, 2004 and2005d;.…”
Section: Ruminal Lipid Metabolismmentioning
confidence: 99%
“…The occurrence of numerous isomers of trans 18:1, Figure 1 Putative pathways describing cis-9 18:1 metabolism in the rumen (adapted from Mosley et al, 2002;Jenkins et al, 2006;McKain et al, 2010). Arrows with solid lines highlight the major biohydrogenation pathway, whereas arrows with dashed lines describe the formation of minor fatty acid metabolites.…”
Section: Ruminal Lipid Metabolismmentioning
confidence: 99%